Legal status of firefighting entities under the new Firefighting Act and some tax observations - Dragan Zlatović; Damir Vlaić (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
Firefighting is a professional non-profit and humanitarian activity aimed at preventing fire protection and technological explosions, i.e. at providing professional technical assistance in the event of fires, explosions and other situations in which there is a threat to human life, the health of the population and material property. Firefighting units and firefighting organizations with their organizational forms participate in the organization and performance of firefighting activities. The fundamental legal regulation of firefighting in the Republic of Croatia is represented by the new Firefighting Act of 2019. The operation of firefighting entities causes a number of open questions from the tax aspect, especially in the case of the performance of certain economic activities by these entities.